Enhancing Black Soybean [Glycine max (L.) Merrill] Yield with Composts and Biofertilizers: A Comprehensive Analysis of Variety- VL Bhat 201 - , Sanchung Lida, Kasinam Doruk, Anki Mibang, Karge Basar, Nabam Akli, Tadang Meena, P. Elavarasi, S. Keerthana (Archives of Current Research International, 2024)
The experiment was conducted in the agriculture field of the Himalayan university, Jollang, Arunachal Pradesh to find out the effect of different composts and biofertilizers inoculations on black soybean yield. The experiment was set up in a Randomized Block Design (RBD) with three replications. Seven different composts and biofertilizers inoculations and one control treatment were used in the study to assess the effect of different composts and biofertilizers on black soybean yield. The findings of the study showed that vermicompost + phosphate solubilizing bacteria and vermicompost + rhizobium inoculant performed better in all aspects of yield components like number of pods per plant, number of seed per pod, seed weight, grain yield, straw yield, biological yield and harvest index etc. However, the control treatment performed lowest in every parameter. As a result of the experiment, it could be concluded that vermicompost + phosphate solubilizing bacteria has a significant effect on yield component of black soybean.